Professional Oracle programming - Greenwald, Rick (Wrox professional guides., 2005)
"If you are a developer who wants to use Oracle to build effective, robust, and scalable software applications, look no further. Written by a team of leading authorities on the Oracle database, this example-packed book is divided into three main areas: how the Oracle database works, how to use SQL and programming languages to access Oracle, and how to use the features of Oracle effectively in creating your applications."--Jacket